The results of treatment in patients with malignant pleural mesothelioma in the Oncology Centre in Cracow - Sas-Korczyńska, Beata; Pęcak, Magdalena; Korzeniowski, Stanisław; Skołyszewski, Jan (Contemporary Oncology/Współczesna Onkologia, 2005)
The aim of this paper is presentation of treatment results in patients with malignant pleural mesothelioma treated in the Oncology Centre in Cracow. Material: Between 1965 and 2003, 63 patients with malignant mesothelioma were treated in the Oncology Centre in Krakow. Grade II or III were observed in 43 patients (64.2%). The surgical treatment was palliative in the majority of patients (84.1%). After this therapy the patients received an adjuvant therapy: chemotherapy and/or radiotherapy. Forty-six patients (73%) received radiotherapy. Since 1991 the mixed beam was used in radiotherapy of malignant mesothelioma. This treatment was performed in 15 patients, and other patients received the photon beam radiotherapy. The range of doses was from 40.5 Gy to 55 Gy. Methods: The 1- and 2-year overall survival rates were estimated with the Kaplan- Meier method. The analysis of prognostic factors was also performed. Results: We observed better results in patients treated from 1991 in comparison with the results observed in patients treated earlier. The analysis of prognostic factors showed that exposure to asbestos and grade III of the clinical stage had a worsening influence on the treatment results. Summary results: A gradual improvement of the treatment results was observed without critical discoveries which radically change the results of oncological treatment.